2015
DOI: 10.1111/nyas.12872
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor‐β in mitochondria: implications for mitochondrial bioenergetics and tumorigenesis

Abstract: Estrogen enhances mitochondrial function by enhancing mitochondrial biogenesis and sustaining mitochondrial energy-transducing capacity. Shifts in mitochondrial bioenergetic pathways from oxidative phosphorylation to glycolysis have been hypothesized to be involved in estrogen-induced tumorigenesis. Studies have shown that mitochondria are an important target of estrogen. Estrogen receptor-β (ERβ) has been shown to localize to mitochondria in a ligand-dependent or -independent manner and can affect mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 93 publications
2
49
0
5
Order By: Relevance
“…Interestingly, a genetic variant of esr2 has been identified as a risk factor of myocardial infraction (Domingues-Montanari et al, 2008). In addition, ERb, a mammalian homologue of esr2a, has recently been found to locate in mitochondria and play bioenergetic roles (Liao et al, 2015). We observed a ~9-fold increase in esr2a expression in female hearts at 7 dpc.…”
mentioning
confidence: 49%
“…Interestingly, a genetic variant of esr2 has been identified as a risk factor of myocardial infraction (Domingues-Montanari et al, 2008). In addition, ERb, a mammalian homologue of esr2a, has recently been found to locate in mitochondria and play bioenergetic roles (Liao et al, 2015). We observed a ~9-fold increase in esr2a expression in female hearts at 7 dpc.…”
mentioning
confidence: 49%
“…In addition, the mitochondrial GR seems to be involved in apoptosis induction in thymocytes, which may not be surprising with regard to the presence of the proapoptotic machinery in this organelle [5]. Mitochondrial localization has been multiply shown for the estrogen receptor-β (ERβ) [6,7], the ER variant anyway known for its nongenomic signaling. In addition to modulation of bioenergetics [6], effects on mitochondrial gene expression were assumed [7].…”
Section: Steroid Tyrosine Hormone and Vitamin D 3 Receptors In Mitomentioning
confidence: 99%
“…Mitochondrial localization has been multiply shown for the estrogen receptor-β (ERβ) [6,7], the ER variant anyway known for its nongenomic signaling. In addition to modulation of bioenergetics [6], effects on mitochondrial gene expression were assumed [7]. Moreover, translocation of the usually genomically acting ERα was reported [8].…”
Section: Steroid Tyrosine Hormone and Vitamin D 3 Receptors In Mitomentioning
confidence: 99%
“…More recently, it has been reported that estrogen also modulates mitochondrial function [2]. Mitochondria are the main source of energy for most cellular activities.…”
mentioning
confidence: 99%
“…The strongest evidence is the finding that estrogen receptor beta binds to estrogen EREs in mtDNA, directly regulating its gene transcription. Moreover, with respect to direct biochemical connection for the role of estrogen in mitochondrial function, treatment of cells with estrogen protects against electron transport chain inhibitors [2]. However, the actions of estrogen on mitochondrial functioning that may underlie this hormone's sex-specific effects on brain development and behavior in schizophrenia remain uninvestigated, and are an important target of research in animal models for the disease.…”
mentioning
confidence: 99%